Social Evolution, Corporate Culture, and Exploitation - Ekkehart Schlicht (Institute for the Study of Labor (IZA), 2002)
It has been claimed that the market fosters selfishness and thereby undermines the moral basis of society. This thesis has been developed with an emphasis on market exchange. Everyday life is, however, predominantly shaped by interactions in the workplace rather than by shopping behaviour. This essay places emphasis on firm organisation, rather than market interaction, in moulding cultural traits. The argument starts with the observation that workers may perceive the employment relationship in two different ways, with different behavioural consequences. The first is the conventional incentive view. The other is the social exchange view. Implementing the social exchange perspective may be profitable for firms which organize complex tasks. This requires an appropriate corporate culture, governed by reciprocity, fairness and commitment. Such a culture can be viewed as a refined form of exploitation, however, as it involves creating an atmosphere of mutuality for profit. I shall argue against this thesis that the same attribution mechanisms which render corporate culture an effective management instrument shape the self-perception of management and engender true, rather than faked, social exchange. The market shapes firm organizations which foster mutualism rather than selfishness.
Keywords: A13; A14; B52; D21; D23; L14; L22; 330; theory of the firm; corporate culture; organizational citizenship; reciprocity; Wirtschaftssoziologie; Kapitalismus; Soziales Verhalten; Unternehmenskultur; Soziale Beziehungen; Kooperative Führung; Theorie